1971
DOI: 10.4039/ent1031137-8
|View full text |Cite
|
Sign up to set email alerts
|

ASSOCIATIVE LEARNING BY NEMERITIS CANESCENS (HYMENOPTERA: ICHNEUMONIDAE)

Abstract: Females of Nemeritis canescens (Grav.) were conditioned to associate the odour of geraniol with the presence of hosts. Females conditioned for 10 days retained the conditioned response for 6 days. Associative learning in N. canescens, an oligophagous parasite, is less strong than in Itoplectis conquisitor (Say), a polyphagous parasite. This finding may reveal a general difference between oligophagous and polyphagous parasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 5 publications
(7 reference statements)
0
25
0
Order By: Relevance
“…Townes (1962) pointed out that the pattern of search does not by itself determine host specificity. Taylor (1974) thus suggested that the proportion of host specificity under genetic control must reside in host acceptance The challenge to the supposition that host searching is under genetic control is brought out by the well documented phenomenon of learning in insects (Alloway 1972) and in the case of insect parasitoids, the work of Thorpe (1938Thorpe ( , 1943, Arthur (1966Arthur ( , 1971, Taylor (1974) and Gross et al (1975). Arthur (1966), working with a non-host specific parasitoid, I. conquisitor, reported that the female learns to concentrate her search to productive habitats.…”
Section: Parasitoid Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Townes (1962) pointed out that the pattern of search does not by itself determine host specificity. Taylor (1974) thus suggested that the proportion of host specificity under genetic control must reside in host acceptance The challenge to the supposition that host searching is under genetic control is brought out by the well documented phenomenon of learning in insects (Alloway 1972) and in the case of insect parasitoids, the work of Thorpe (1938Thorpe ( , 1943, Arthur (1966Arthur ( , 1971, Taylor (1974) and Gross et al (1975). Arthur (1966), working with a non-host specific parasitoid, I. conquisitor, reported that the female learns to concentrate her search to productive habitats.…”
Section: Parasitoid Conditioningmentioning
confidence: 99%
“…Arthur (1966), working with a non-host specific parasitoid, I. conquisitor, reported that the female learns to concentrate her search to productive habitats. In a later paper (Arthur 1971) using a host-specific parasitoid, V. canescens, showed that the female could be conditioned to associate a "normal" odor with the presence of hosts. Taylor (1974) expanded on the above studies using V. canescens and showed that the female can learn to hunt hosts in a novel environment and that a model using the learning of two cues fits better than a model using only one.…”
Section: Parasitoid Conditioningmentioning
confidence: 99%
“…For clarity I use the terms oligophagous and polyphagous to describe herbivore diet breadth. Diet specialization is relative and may be affected by local ecological conditions (Fox & Morrow 1981), population density (Zwolfer 1971), or even individual experience (Arthur 1971, Vet 1983). Despite such difficulties, the concept of diet specialization is heuristic.…”
mentioning
confidence: 99%
“…The second step in the host finding process is host location and involves close range cues (Lewis & Jones, 1971 ;Jones et al, 1971 ;Sauls et al, 1979 ;Nordlund & Sauls, 1981). Additionally, parasitoid learning may play a role in the host finding process (Arthur, 1966(Arthur, , 1971Drost et al, 1988, Kaas, 1990. Host derived products have been demonstrated to influence parasitoid behavior (Whitman, 1988).…”
Section: Discussionmentioning
confidence: 99%